2011
DOI: 10.1007/s12011-011-9080-3
|View full text |Cite
|
Sign up to set email alerts
|

Low Concentrations of Selenium and Zinc in Nails are Associated with Childhood Asthma

Abstract: The purpose of this study was to investigate possible associations between Zn, Se, Cu, Mn, and Co concentrations in nails and asthma in a young population from a Southern Brazil city. Additionally, correlations between these chemical elements among asthmatic and non-asthmatic children were evaluated. Before nail collection (n = 165), children were asked to complete the International Study of Asthma and Allergies in Childhood questionnaire. The concentrations of trace elements were determined by inductively cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 33 publications
2
25
1
Order By: Relevance
“…The immunomodulatory properties and effective therapeutic potential of Se for the treatment of asthma has drawn attention of researchers in recent years (2,50,51). However, available dietary Se supplements mainly consist of two inorganic forms, sodium selenate and sodium selenite, and one organic form, selenomethionine.…”
Section: Resultsmentioning
confidence: 99%
“…The immunomodulatory properties and effective therapeutic potential of Se for the treatment of asthma has drawn attention of researchers in recent years (2,50,51). However, available dietary Se supplements mainly consist of two inorganic forms, sodium selenate and sodium selenite, and one organic form, selenomethionine.…”
Section: Resultsmentioning
confidence: 99%
“…Zinc deficiency may exacerbate airway inflammation in asthma. 47 Some studies show an association between low zinc levels and asthma, [48][49][50][51][52] while others contradict these findings, [53][54][55][56] and systematic review evidence is lacking. One study found no relationship between allergic rhinitis and plasma zinc and another study found no relationship between allergic rhinitis and dietary zinc intake.…”
Section: Discussionmentioning
confidence: 99%
“…Many diseases have been associated with lack of the essential trace element Se in the body, including asthma, rheumatoid arthritis, and cancer[26-28]. In these diseases, Se deficiency is abnormal, making supplementation with exogenous Se a reasonable method of treatment.…”
Section: Discussionmentioning
confidence: 99%